Implementation of Models of Care for secondary osteoporotic fracture prevention and orthogeriatric Models of Care for osteoporotic hip fracture - Mitchell, P; Åkesson, K; Chandran, M; Cooper, C; Ganda, K; Schneider, M (Elsevier, 2016)
As the world's population ages, the prevalence of osteoporosis and its resultant fragility fractures is set to increase dramatically. This chapter focuses on current frameworks and major initiatives related to the implementation of fracture liaison services (FLS) and orthogeriatrics services (OGS), Models of Care designed to reliably implement secondary fracture prevention measures for individuals presenting to health services with fragility fractures. The current evidence base regarding the impact and effectiveness of FLS and OGS is also considered.